Communicating complex numeric information in clinical research - Bierer, Barbara E.; Baedorf Kassis, Sylvia (Frontiers in Communication, 2023)
The ability to understand and use numeric information in healthcare and clinical research is a critical component of informed decision-making for patients and study participants. Health numeracy levels in the general population, however, tend to be quite low and as such, the responsibility falls on communicators to ensure that the information being shared is designed to facilitate recipient comprehension and support their autonomy. Here, we introduce health numeracy considerations within the clinical research context and outline specific areas that can benefit from thoughtful communication strategies, including the presentation of visual information to augment the interpretation of, and learning about, research studies. Specifically, we discuss seven categories of numeric concepts that arise throughout the course of research participation and important considerations when presenting such information. Increasing awareness amongst communicators about health numeracy and the need to include supportive visual representations when developing and sharing clinical research-related information will help support the creation of tailored information that meet the needs of the intended audience.